2020
DOI: 10.1186/s13071-020-04319-4
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of feline intestinal parasites: trends in testing positivity by age, USA geographical region and reason for veterinary visit

Abstract: Background The goals of this retrospective study were to estimate parasite positivity in samples from cats using zinc sulfate fecal flotation by centrifugation (“centrifugation”) and coproantigen and examine trends with age, geographical region and reason for visit to veterinarian. Common methods of parasite detection, such as centrifugal flotation, passive flotation, or direct smear, may underrepresent the true prevalence of intestinal parasites in cats. Coproantigen testing detects more positive samples than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…In this study, the parasite with the highest preva-lence was Giardia species followed by Cryptosporidium species, T cati, Cystoisospora species and D caninum. These results coincide with the results of a similar scope study conducted in Poland, 15,16 which showed that Giardia species are the most common parasites in cats. Nevertheless, our results differ from the results of Little et al, 17 which indicated that T cati is the most common parasite (found in up to 40% of the total study population).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the parasite with the highest preva-lence was Giardia species followed by Cryptosporidium species, T cati, Cystoisospora species and D caninum. These results coincide with the results of a similar scope study conducted in Poland, 15,16 which showed that Giardia species are the most common parasites in cats. Nevertheless, our results differ from the results of Little et al, 17 which indicated that T cati is the most common parasite (found in up to 40% of the total study population).…”
Section: Discussionsupporting
confidence: 91%
“…Seasonality of parasite infection in cats has been evaluated mostly in retrospective, longitudinal studies [ 12 , 13 ]. It is possible that sampling and analysis over a fixed period of time may provide more useful information on the current effects of season on parasite prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a study assessing intestinal parasites from 3006 dog fecal samples collected in 288 off-leash dog parks across the USA in 2019, the prevalence of A. caninum was 7.1% (Stafford et al, 2020). Interestingly, this prevalence is more than twice as high as that reported for 2018 by (Drake and Carey, 2019), and is more than 70% higher than the mean prevalence for 2017-2019 reported by (Sweet et al, 2021). Taken together these data suggest that hookworm prevalence is rapidly increasing, and that dogs that visit dog parks are at a higher risk of infection.…”
Section: Introductionmentioning
confidence: 48%
“…The almost ubiquitous presence of MDR worms in recently retired greyhounds, combined with the demise of the greyhound racing industry and increasing numbers of greyhound adoptions, poses a serious risk to the health of pet dogs. From 2009-2019, the number of dog parks increased by 74% in the USA (TPL, 2019), and a recent survey showed that the prevalence of A. caninum in dogs visiting these parks (Stafford et al, 2020) was more than 70% higher as compared to the prevalence in all pet dogs recorded over the same general timeframe (Sweet et al, 2021). These relative prevalence data should not be surprising; a fecal pile deposited by a 30 kg dog with an A. caninum FEC of ∼1000 EPG will contain approximately 500,000 eggs.…”
Section: Discussionmentioning
confidence: 99%